Desafíos de los líderes comunitarios en la conservación de los recursos naturales en comunidades afiliadas a la federación Feconamncua. Loreto 2024 - Ugkum Jempets, Adiazar (2025)
The research analyzes the challenges faced by community leaders in the conservation of natural resources in communities affiliated with FECONAMNCUA, Loreto, Peru. Issues such as deforestation, biodiversity loss, lack of land titling, and limited community participation were identified. Based on a mixed-methods approach and a theoretical framework on community leadership and conservation, the results show that 66.7% of leaders perceive conservation efforts as inadequate, and 91.11% consider current practices insufficient. It is concluded that structural and organizational barriers limit the leaders' capacity, highlighting the need to strengthen territorial governance, implement training programs, and foster strategic alliances to promote environmental sustainability.